Cortisol promotes the cognitive regulation of high intensive emotions independent of timing. (27th March 2021) - Langer, Katja; Jentsch, Valerie L.; Wolf, Oliver T.
Abstract: Failures to cognitively downregulate negative emotions are a crucial risk factor for mental disorders. Previous studies provide evidence for a stress‐induced improvement of cognitive emotion regulation possibly mediated via glucocorticoid actions. Cortisol can initialize immediate non‐genomic as well as delayed genomic effects on cognitive control functioning, but its distinct effects on emotion regulation processes remain to be shown. Here, we sought to characterize time‐dependent effects of oral cortisol administration on cognitive emotion regulation outcomes. We expected cortisol to improve emotion regulation success. Possible interactions with the delay between cortisol treatment and emotion regulation, strategy use and intensity of the emotional stimuli were examined. Eighty‐five healthy men received either 10 mg hydrocortisone or a placebo in a double‐blind, randomized design 30 or 90 min prior to an emotion regulation paradigm, in which they were asked to downregulate their emotional responses towards low and high intensive negative pictures via reappraisal or distraction. Affective ratings and pupil dilation served as outcome measures. Reduced arousal, enhanced valence ratings as well as increases in pupil dilations indexing the cognitive regulatory effort indicated successful downregulation of negative emotions evoked by high intensive but not low intensive negative pictures. Cortisol significantly reduced arousal ratings when downregulating high intensive negative emotions via distraction and (at a trend level) via reappraisal, independent of timing, demonstrating a beneficial effect of cortisol on subjective regulatory outcomes. Taken together, this study provides initial evidence suggesting that cortisol promotes the cognitive control of high intensive negative emotions both, 30 and 90 min after treatment. Abstract : This study indicates that cortisol may foster the cognitive downregulation of high intensive but not of low intensive negative emotions. However, cortisol effects neither interact with the delay between tablet intake and emotion regulation nor with strategy use.